Issues on Early Marriage among Female Adolescents in Isi-Uzo Local Government Area, Enugu State - N.P, Owoh; O. I, Okoye; C. A, Nwobi; F.O, Okechukwu (Journal of Home Economics Research, 2024)
This study investigated issues on early marriage among female adolescents in Isi-Uzo Local Government Area (LGA) of Enugu state. Specially, it identified causes and challenges of female adolescent marriage, as well as ways of preventing the practice in the study area. Questionnaire and focus group discussion guide were utilized for data collection. Population for study was 3, 713 adolescents and their mothers. Data were analyzed using means for quantitative data while qualitativedata were summarised. Major findings include causes of female adolescent marriage. These include, ignorance, poverty and among others, fourteen (14) challenges identified, including, maritual instability, poor health and among others. Ten ways of stopping the practice were identified. These include, provision of free education for youths and orientation program for the youths. Many of the qualitative findings collaborate the quantitative findings. Based on the findings, three recommendations were made for prevention of female adolescent marriage in Isi-uzo LGA of Enugu state.